Functional Outcome of Biportal Endoscopy Spine Surgery for Lumbar Disc Herniation Diseases - Risdianto, Ajid; Andar, Erie; Brotoarianto, Happy Kurnia; Priambada, Dody; Muttaqin, Zainal; Prihastomo, Krisna Tsaniadi; Bakthiar, Yuriz; Arifin, Muhammad Thohar (Majalah Kedokteran Bandung, 2025)
Biportal endoscopic spine surgery (BESS) is an innovative, minimally invasive technique to treat lumbar disc herniation (LDH). BESS provides superior surgical visualization with minimal tissue dissection. However, its application requires a thorough understanding of endoscopic anatomy and adaptation of endoscopy equipment, which are key factors in achieving optimal functional outcomes post-surgery. This study aimed to evaluate the functional outcomes and complications of BESS performed on 49 patients between 2020 and 2022 at Dr. Kariadi Hospital, Semarang, Indonesia. The majority of patients (53%) had herniation at the L4-5 level, followed by L5-S1. Pain assessment using the Visual Analog Scale (VAS) demonstrated a significant reduction in pain, from 4.26 to 1.5, post-surgery. Functional outcomes, as evaluated using MacNab’s Criteria, revealed that 93.8% of patients achieved a satisfactory condition, with 36.7% reporting no pain and 57.1% experiencing occasional pain that did not affect their daily activities. Complications were minimal, with two cases of dural tears and intraoperative bleeding. The study concludes that BESS is a safe and effective procedure for LDH, resulting in significant pain relief and functional improvement, although certain technical challenges persist.